Quality Practices and Accreditation in Higher Education Institutions: A Roadmap for Excellence in Engineering Education - Siddapuram, Arvind; SV, Devika; Bonkuri, Abhinesh (Journal of Engineering Education Transformations, 2025)
In the current scenario of educational system, there is an increasing demand for higher education in India. Particularly, there is exponential growth and competition visible among Engineering Institutions in coming days. To stand out, it is very important for undergraduate educational institutions to maintain high-quality standards. Accreditations like NAAC and NBA has emerged as potential tool for assuring the quality of educational institutions in India. Stakeholders started believing in these scores to judge the performance of the Institutions. Hence, it is mandatory for Higher Educational Institutions to maintain the high-quality standards will not only help in getting accreditation but also helps in the growth of the Institution. This paper presents the quality practices to be followed by the educational institutions to achieve maximum accreditation scores. A new mantra which has 10 key points are proposed in this paper which will help the higher educational institutions to follow it as a road map for achieving excellence in Engineering Education.